Konflik Batin Tokoh Utama Perempuan dalam Novel Cinta Suci Zahrana Karya Habiburrahman El Shirazy - Arisa; Nur Rahmi; Rudi Karma; Muh. Damriansyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2021)
Abstract: The Inner Conflict of the Female Lead in Habiburrahman El Shirazy's Novel Zahrana Holy Love. This research was motivated by the researcher's desire to study the novel Holy Love Zahrana by Habiburrahman El Shirazy because it was considered very interesting to be researched because the story presents an inner conflict that makes Zahrana depressed. The inner conflict of the female protagonist in the novel Holy Love Zahrana by Habiburrahman El Shirazy is based on a study of literary psychology. The purpose of this study is to describe the picture of the inner conflict of the female main character which includes approaching conflicts, approaching conflicts away, distant conflicts, and the relevance of inner conflicts to character education in the novel Holy Love Zahrana by Habiburrahman El Shirazy.The resulting data is in the form of words, phrases and sentences contained in the novel. The type of research is qualitative descriptive with a literary psychology approach. The data collection technique used is a reading and recording technique. The data processing techniques used are collection, selection, and organization. The data analysis technique used is a content analysis technique. The technique of checking the validity of research used triangulation is, intensive discussion and guidance. The results of this study show that in the novel Holy Love Zahrana there is an inner conflict consisting of, 1) nearing conflict, 2) approaching conflict away, 3) distant conflict, and 4) the relevance of inner conflict to character education. Based on the results of data analysis, it can be concluded that the overall data obtained were 24 data with the most data on inner conflicts approaching as many as 10 data, on approaching away as many as 6 data, the relevance of inner conflicts to character education as many as 5 data, and conflicts away from 3 data.